Psychiatric and behavioral side effects of anti-epileptic drugs in adolescents and children with epilepsy. (May 2017) - Chen, B.; Detyniecki, K.; Choi, H.; Hirsch, L.; Katz, A.; Legge, A.; Wong, R.; Jiang, A.; Buchsbaum, R.; Farooque, P.
Abstract: Purpose: The objective of the study was to compare the psychiatric and behavioral side effect (PBSE) profiles of both older and newer antiepileptic drugs (AEDs) in children and adolescent patients with epilepsy. Method: We used logistic regression analysis to test the correlation between 83 non-AED/patient related potential predictor variables and the rate of PBSE. We then compared for each AED the rate of PBSEs and the rate of PBSEs that led to intolerability (IPBSE) while controlling for non-AED predictors of PBSEs. Results: 922 patients (≤18 years old) were included in our study. PBSEs and IPBSEs occurred in 13.8% and 11.2% of patients, respectively. Overall, a history of psychiatric condition, absence seizures, intractable epilepsy, and frontal lobe epilepsy were significantly associated with increased PBSE rates. Levetiracetam (LEV) had the greatest PBSE rate (16.2%). This was significantly higher compared to other AEDs. LEV was also significantly associated with a high rate of IPBSEs (13.4%) and dose-decrease rates due to IPBSE (6.7%). Zonisamide (ZNS) was associated with significantly higher cessation rate due to IPBSE (9.1%) compared to other AEDs. Conclusion: Patients with a history of psychiatric condition, absence seizures, intractable epilepsy, or frontal lobe epilepsy are more likely to develop PBSE. PBSEs appear to occur more frequently in adolescent and children patients taking LEV compared to other AEDs. LEV-attributed PBSEs are more likely to be associated with intolerability and subsequent decrease in dose. The rate of ZNS-attributed IPBSEs is more likely to be associated with complete cessation of AED. Highlights: Psychiatric/behavioral side effects of AEDs are compared in pediatric patients. Psychiatric history and intractable epilepsy are associated with higher PBSE rates. Absence seizures and frontal lobe epilepsy are associated with higher PBSE rates. Levetiracetam use is associated with higher PBSE incidence in pediatric patients. Zonisamide use is associated with higher cessation rate secondary to PBSE.